siRNA Design Software for a Target Gene-Specific RNA Interference - Naito, Yuki; Ui-Tei, Kumiko (Frontiers in Genetics, 2012)
RNA interference (RNAi) is the mechanism through which small interfering RNA (siRNA) induces sequence-specific posttranscriptional gene silencing. RNAi is commonly recognized as a powerful tool not only for functional genomics but also for therapeutic applications. Twenty one-nucleotide-long siRNA suppresses the expression of the intended gene whose transcript possesses perfect complementarity to the siRNA guide strand. Hence, its silencing effect has been assumed to be extremely specific. However, accumulated evidences revealed that siRNA could downregulate unintended genes with partial complementarities mainly to the 7-nucleotide seed region of siRNA. This phenomenon is referred to as off-target effect. We have revealed that the capability to induce off-target effect is strongly correlated to the thermodynamic stability in siRNA seed-target duplex. For understanding accurate target gene function and successful therapeutic application, it may be critical to select a target gene-specific siRNA with minimized off-target effect. Here we present our siRNA design software for a target-specific RNAi. In addition, we also introduce the softwares open to the public for designing functional siRNAs.